Ambiguity in human communication: causes, consequences and resolution - S.O. Oluga B.A.; P.G.D; M.A. (2010)
Effective communication is not just about the transmission of ideas/messages from the sender to the receiver. Rather, it is about the dissemination of properly worded meaningful ideas/messages that are comprehensible to both parties and which ultimately can attract the desired response or feedback. Semantic clarity therefore, is very essential to the effectiveness of communication which facilitates the attainment of target goals. Ambiguity however, has a way of intruding into communication and subjecting ideas/messages to double or multiple semantic interpretations thereby resulting in semantic complexity and sometimes leading to semantic confusion. Proper disambiguation however, remains the only antidote to the semantic problem of ambiguous communication. This paper therefore, highlights causes of ambiguity in human communication. It analyses its possible consequences. Finally, it explicates appropriate ambiguity resolution techniques as linguistic panacea.